Jazz Books in The 1990s: An Annotated Bibliography - Greenberg, Janice Leslie Hochstat (Rowman & Littlefield Publishers, 2010)
Jazz Books in the 1990s: An Annotated Bibliography contains over 700 entries covering adult non-fiction books on jazz published from 1990 through 1999. International in scope, the books included range from such places as Finland, Slovakia, Australia, Japan, India, and South Africa, as well as Canada, the United Kingdom, and the United States. Entries are organized by category, including biographies, history, individual instruments, essays and criticism, musicology, regional studies, discographies, and reference works. Greenberg has amassed an impressive collection of entries with each entry including the author, title, publisher, year, and number of pages, and also indicating when a book contains a bibliography, discography, footnotes, musical transcriptions, illustrations, photographs, or any other additional material. The discography entries also note whether books contain unissued material or reissues. Three indexes—by title, author, and subject—make this a valuable and comprehensive reference guide for researchers, students, and jazz aficionados alike.